2017
DOI: 10.1038/s41598-017-05474-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescent probe-based flow cytometric assay for mineral-containing nanoparticles in serum

Abstract: Calciprotein particles, nanoscale aggregates of insoluble mineral and binding proteins, have emerged as potential mediators of phosphate toxicity in patients with Chronic Kidney Disease. Although existing immunochemical methods for their detection have provided compelling data, these approaches are indirect, lack specificity and are subject to a number of other technical and theoretical shortcomings. Here we have developed a rapid homogeneous fluorescent probe-based flow cytometric method for the detection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 92 publications
(113 reference statements)
4
87
1
7
Order By: Relevance
“…Chronic exposure to CPPs, e.g., when clearance becomes overwhelmed as in CKD, is a likely driver of VC 24 . CPPs were found to be present in serum from high-phosphate-diet-fed rats with adenine-induced renal failure 72 . By stabilizing CPPs, (OEG 2 ) 2 -IP4 may aid mineral clearance from the circulation before VC can ensue.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic exposure to CPPs, e.g., when clearance becomes overwhelmed as in CKD, is a likely driver of VC 24 . CPPs were found to be present in serum from high-phosphate-diet-fed rats with adenine-induced renal failure 72 . By stabilizing CPPs, (OEG 2 ) 2 -IP4 may aid mineral clearance from the circulation before VC can ensue.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we reported finding only copious amounts of secondary CPP in post-mortem ascites of a peritoneal dialysis patient who had died of sclerosing peritonitis ( 24 ). Other studies indicate that secondary CPP, while occasionally observed in serum and peritoneal effluent of dialysis patients, are present in much lower amounts than primary CPP ( 25 ). Thus, it remained of critical importance to understand the handling and effects of primary CPP in comparison with their more stable crystalline counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the accumulation of fetuin-A-containing mineral particles was noted in the peritoneal dialysate of a patient suffering from calcifying peritonitis [10] and in patients suffering from chronic kidney disease (CKD) [11]. Recent work has shown that both the abundance of CPP [12][13][14] and the kinetics of CPP formation [15][16][17][18] in serum of CKD patients can be used to monitor the propensity for calcification of these patients. The function of fetuin-A as an inhibitor of calcification is underscored by clinical studies showing that low fetuin-A serum levels are associated with calcification disease [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%